Pengembangan Smart Modul Tema 8 ”Manusia dan Lingkungan“ Untuk Kelas V Sekolah Dasar - Octavia Tri Anggraini; Erwin Putera Permana; Farida Nurlaila Zunaidah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research is backgrounded by the results of observations obtained, namely the use of learning media used by teachers is predominantly monotonous and makes students feel saturated or bored to learn. With these problems, researchers develop smart module teaching materials to assist teachers in providing material to students so that students can understand the material well. This study aims to (1) find out the validity of the development of human module smart teaching materials and the environment, (2) know the practicality of human module smart teaching materials and the environment for class V elementary schools and, (3) know the effectiveness of the smart module teaching materials